The Impact of Demographic Change on Tourism in North Oltenia Region - Iulian Adrian SORCARU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2017)
Tourism in any region is closely linked to its demographic potential. North Oltenia is known in Romania for its valuable tourism potential, both natural and anthropic, which caused over time a contiuous diversification of the types of tourism. This study deals with the demographic evolution of the administrative units in North Oltenia, between Tismana and Olt Rivers in the last half of century (1966-2015), analyzing also the age structure and demographic ageing after 1990. The major objectives of this study were to identify the types of demographic change and the hierarchy of the administrative units; the analysis of age structure (youth, adults, elders), especially adults who include the working population capable of sustaining tourist flows in the region and demographic ageing. Mapping the results was designed to quickly identify the administrative units where demographic potential recorded an unfavorable evolution, where tourism potential and maintenance of the existing tourism infrastructure can be more difficult in the future.